Breeding Strategy of Ornamental Fish, Sword Tail (Xiphophoru shelleri) & Sawdust Molly (Poecilia sphenops) under Captive Condition - Dwivedi, Prakriti; Dhyani, Prerna; Rawat, Anupam; Uniyal, Beena (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
An experiment was conducted over a period of 4 to 6 weeks (February to April 2023) in glass aquariums and tanks within the laboratory of the Forestry and Fisheries Department to study the comparative breeding techniques of two ornamental fish species: Swordtail (Xiphophorus hellerii) and Sawdust Molly (Poecilia sphenops). Breeding pairs were introduced at ratios of 2:1 for Swordtail and 2:3 for Sawdust Molly. Successful breeding of Swordtail was recorded in March 2023, with the observation of 8 live fry in the aquarium. These fry were subsequently transferred to a separate tank equipped with a bubble diffuser to facilitate respiration and were fed crushed feed suitable for their size. The first mortality of a pregnant Swordtail was observed in April 2023. Upon dissection, 38 undeveloped fry were recovered. Breeding in Sawdust Molly was observed later in April 2023, yielding a total of 14.